HUBUNGAN PEMBERIAN KIE DENGAN PENGETAHUAN NUTRISI MASA NIFAS DI PUSKESMAS KEDUNGDUNG SAMPANG - Nikmah, Nurun (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The postpartum period is an important period in the life of a mother, especially during the first puerperium. Adequate nutrition and quality consumed by postpartum mothers greatly affect health. This study aims to determine the relationship of providing KIE (Communication, Information, and Education) with nutrition knowledge during the puerperium. This type of research is analytic, with the population is 38 trimester III pregnant women, Samples counted 35 people with simple random sampling technique. The independent variable is the provision of KIE and the dependent variable is the puerperal nutrition knowledge. Methods of data collection using questionnaire and analyzed using spearman's rho statistical test with Î± = 0.05. The results showed that the samples given KIE as much as 51.4% and that is not given KIE of 48.6%. Good knowledge 42.9%, enough 14.3%, and less 42.9%. The result of statistic test shows that p <Î± is (0.0001 < 0.05) which means that there is a relationship of KIE with knowledge about postpartum nutrition. Keywords: Knowledge, Nutrition, Puerperium, Communication